Design of Paired Pouch Motors for Robotic Applications. Issue 1 (22nd October 2018) - Oh, Namsoo; Park, Yeong Jae; Lee, Seongbok; Lee, Haneol; Rodrigue, Hugo
Abstract: The performance of soft linear actuators will determine the capabilities of future soft robots, and any actuator that can produce larger deformations and forces with a low weight and using lower pressures could potentially become ubiquitous in the field. In this work, the design of paired pouch motors that can produce a maximum contraction ratio of 41.9% and of 31% with a 10 kg payload is presented. The design of higher‐order pairings of pouch motors is demonstrated to produce even larger deformations, and this basic concept is also applied to serial pneumatic artificial muscles to produce a contraction ratio as high as 51.78%. This concept can be applied to other soft actuators that produce a lateral expansion to produce a longitudinal contraction. Paired pouch motors are also applied to a jointed soft robotic arm where a single pouch motor is sufficient to produce a joint deformation of 120° at a pressure of 100 kPa with a tip payload of 300 g. Paired pouch motors have a combination of characteristics including ease of manufacturing, low weight, and low cost paired with good actuation performance that could make it one of the leading actuator design in the field of soft robotics. Abstract : Paired pouch motors capable of contraction ratios up to 41.9% are introduced, and the concept of pairing linear actuator for increased performance is extended to higher‐order pairs for pouch motors and serial pneumatic artificial muscles. With their low weight and good performance, these paired pouch motors can have good performance as part of a robotic arm.